2017
DOI: 10.1080/15438627.2017.1314290
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological survey of anterior cruciate ligament injury in Japanese junior high school and high school athletes: cross-sectional study

Abstract: We investigated the incidence of anterior cruciate ligament (ACL) injuries among athletes in junior high school and high school by retrospectively reviewing Japan Sports Council notification data registered over a period of 10 years. The total number of ACL injuries during the 10-year period was 30,458, with an incidence of 0.81 per 1000 athlete-years. Among those with ACL injuries, the ratio of girls to boys was 2.8, and incidence of injury was significantly greater among girls than boys (1.36 as against 0.48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…The model was passively simulated in the three independent rotations to study the strains on individual connective tissues. Mechanism of sports injuries [ 8 , 21 , 22 , 36 ] and injuries in elderly [ 5 , 15 , 28 ] are lucidly credible with the help of the proposed model.…”
Section: Discussionmentioning
confidence: 99%
“…The model was passively simulated in the three independent rotations to study the strains on individual connective tissues. Mechanism of sports injuries [ 8 , 21 , 22 , 36 ] and injuries in elderly [ 5 , 15 , 28 ] are lucidly credible with the help of the proposed model.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research also revealed that high school students have a high rate of ACL injuries compared to junior high school age groups. [13] Therefore, it is necessary to investigate mechanisms of ACL injury among high school students within each sport to gain a better understanding of ACL injury patterns and injury prevention.…”
Section: Introductionmentioning
confidence: 99%
“…In soccer, the injury rate for ACL varies from 0.07 to 0.5 injuries per 1000 player-hours [40][41][42]. According to Takahashi et al, the incidence of ACL injuries in judo is 0.81 per 1000 athlete-years [43]. These results demonstrate that ACL injuries in judo are common (even more than in soccer) and that medical teams should be fully prepared in order to give athletes the best care to return to competition as safely as possible.…”
Section: Discussionmentioning
confidence: 99%